Downregulation of CISD2 Has Prognostic Value in Non-Small Cell Lung Cancer and Inhibits the Tumorigenesis by Inducing Mitochondrial Dysfunction - Shao, Fangchun; Li, Yanchun; Hu, Wanye; Yu, Jiaqi; Wu, HengYu; Ying, Kejing; Xia, Jun; Du, Jing (Frontiers in Oncology, 2021)
CISD2, a NEET protein that coordinates 2Fe-2S clusters through its CDGSH domain, is critical for normal development and iron homeostasis. CISD2 plays an important role in Fe-S cluster transfer and promotes cancer proliferation. However, its specific role in the development of non-small cell lung cancer (NSCLC) remains unclear. Bioinformatics of pan-cancer analysis from The Cancer Genome Atlas show that CISD2 has an aberrant expression in most types of human cancers. Moreover, CISD2 expression is associated with a higher hazard ratio and exhibits significantly poorer overall survival in lung adenocarcinoma (LUAD), uveal melanoma, head and neck squamous cell carcinoma, brain lower grade glioma, kidney chromophobe, and liver hepatocellular carcinoma. Further investigation revealed that CISD2 is highly expressed in LUAD and LUSC, which is associated with clinical pathological stages. In addition, survival data collected from GSE31210 and GSE13213, two datasets from the NCBI Gene Expression Omnibus, also confirmed that high CISD2 expression is associated with unfavorable survival in patients with LUAD. A cell-based assay indicated that the knockdown of CISD2 inhibited proliferation, invasion, and migration in A549 cells. Additionally, CISD2 knockdown accelerated the accumulation of cellular and mitochondrial reactive oxygen species, destroying the mitochondrial morphology and function. Moreover, CISD2 inhibition activated the iron starvation response, thus, accelerating iron accumulation in A549 cells. Pretreatment with DFO, the iron chelator, blocked mitochondrial dysfunction in CISD2-knockdown cells. Collectively, the present study provides novel insights into the regulatory role of CISD2 in NSCLC and presents a potential target to improve antitumor activity based on oxidative stress.